Production of volatile compounds by a variety of fungi in artificially inoculated and naturally infected aquilaria malaccensis - Aizi Nor Mazila, Ramli; Sufihana, Yusof; Bhuyar, Prakash; Aimi Wahidah, Aminan; Saiful Nizam, Tajuddin; Hazrulrizawati, Abd Hamid (Springer, 2022)
Aquilaria malaccensis, the resinous agarwood, is highly valued in the perfumery and medicinal industry. The formation of fragrant agarwood resin inconsistently by various fungi is still not clearly understood. The current study investigated the agarwood quality and fungal diversity in artificially inoculated and naturally infected A. malaccensis. The chemical analysis of volatile compounds of agarwood was performed using the Solid Phase Micro Extraction (SPME) method, and the identification of fungi was made through a morphological observation using a light microscope. Gas chromatography analysis revealed the presence of essential compounds related to high-quality agarwood, such as 4-phenyl-2-butanone, β-selinene, α-bulnesene, and agarospirol in both artificially inoculated and naturally infected agarwood but with some differences in the abundance. Further studies on the fungi associated with agarwood volatile compounds formation showed a total of ten fungal group isolates, which were identified based on morphological and molecular studies. The study revealed that agarwood from both artificial and natural sources were naturally infected with Fusarium, Botryosphaeria, Aspergillus, Schizophyllum, Phanerochaete, Lasiodiplodia, Polyporales, and Ceriporia species. This study has offered a potential opportunity to research further the promising development of fungal strains for artificial inducement of high-quality agarwood formation from A. malaccensis trees.